Excited‐State Aromaticity of Gold(III) Hexaphyrins and Metalation Effect Investigated by Time‐Resolved Electronic and Vibrational Spectroscopy. (4th February 2020) - Kim, Jinseok; Oh, Juwon; Soya, Takanori; Yoneda, Tomoki; Park, Seongchul; Lim, Manho; Osuka, Atsuhiro; Kim, Dongho
Abstract: Expanded porphyrins with appropriate metalation provide an excellent opportunity to study excited‐state aromaticity. The coordinated metal allows the excited‐state aromaticity in the triplet state to be detected through the heavy‐atom effect, but other metalation effects on the excited‐state aromaticity were ambiguous. Herein, the excited‐state aromaticity of gold(III) hexaphyrins through the relaxation dynamics was revealed via electronic and vibrational spectroscopy. The SQ states of gold [26]‐ and [28]‐hexaphyrins showed interconvertible absorption and IR spectra with those of counterparts in the ground‐state, indicating aromaticity reversal. Furthermore, while the T1 states of gold [28]‐hexaphyrins also exhibited reversed aromaticity according to Baird's rule, the ligand‐to‐metal charge‐transfer state of gold [26]‐hexaphyrins contributed by the gold metal showed non‐aromatic features arising from the odd‐number of π‐electrons. Abstract : Die Umkehrung der Aromatizität im angeregten Zustand von Gold‐koordinierten Hexaphyrinen wird durch Schwingungs‐ und elektronische Strukturanalysen aufgedeckt. Die durch die Aromatisierungsumkehr angetriebenen Strukturänderungen und invertierten elektronischen Strukturen wurden ebenfalls nachgewiesen.